An iron ketimide single-molecule magnet [Fe4(NCPh2)6] with suppressed through-barrier relaxation. Issue 18 (28th April 2020) - Cook, Andrew W.; Bocarsly, Joshua D.; Lewis, Richard A.; Touchton, Alexander J.; Morochnik, Simona; Hayton, Trevor W.
Abstract : The tetrametallic Fe ketimide cluster, [Fe4 (NCPh2 )6 ], exhibits a thermally persistent S = 7 ground-state along with single molecule magnet behavior. Abstract : Reaction of FeBr2 with 1.5 equiv. of LiNCPh2 and 2 equiv. of Zn, in THF, results in the formation of the tetrametallic iron ketimide cluster [Fe4 (NCPh2 )6 ] (1 ) in moderate yield. Formally, two Fe centers in 1 are Fe(i ) and two are Fe(ii ); however, Mössbauer spectroscopy and SQUID magnetometry suggests that the [Fe4 ] 6+ core of 1 exhibits complete valence electron delocalization, with a thermally-persistent spin ground state of S = 7. AC and DC SQUID magnetometry reveals the presence of slow magnetic relaxation in 1, indicative of single-molecule magnetic (SMM) behaviour with a relaxation barrier of U eff = 29 cm −1 . Remarkably, very little quantum tunnelling or Raman relaxation is observed down to 1.8 K, which leads to an open hysteresis loop and long relaxation times (up to 34 s at 1.8 K and zero field and 440 s at 1.67 kOe). These results suggest that transition metal ketimide clusters represent a promising avenue to create long-lifetime single molecule magnets.